On Signal Decrease in HF Circuits During PCA Events - Wong, Ming S (1973)
The principal morphological features of ionospheric absorption of cosmic radio noise at vertical incidence -due to influx into the polar ionosphere of solar protons with particle energy near 10 MeV, and as measured by ground-based riometers operated usually at 30 MHz- are reviewed with figures and brief descriptions. HF signal-intensity observations in two oblique-incidence circuits, Thule to College and Pt. Barrow to Kenai (Alaska), are compared with riometer measurements for several PCA events. It is suggested that a 'stand-by' propagation mode, involving a combination of scattering and ducting of HF radio waves near the ionospheric-bottom-boundary, comes into play. It is also suggested that, during disturbed inospheric conditions, diminutions in ionospheric electron density -in addition to, or in conjunction with, increased ionospheric absorption- is an important contributing cause to HF radio blackouts.